The Toll of Emotional Labor in Job Searches for PhD Graduates: Challenges and Insights - Katherine T. Chapman; Cheryl Kennedy (Adult Education Research Conference, 2025)
Using emotional labor theory as a lens, this study seeks to provide college faculty mentors with insight into the phenomenon of emotional labor experienced by doctoral students transitioning into a career.
Keywords: Emotional Labor; Emotional Labor Theory; Emotion Work